(untitled) (Mustansiria Dental Journal, 2018)
The dirty denture may have undesirable effect on patient’s health and ability to successful wear of the denture, if a patient’s denture becomes unsanitary, the consequences may be bad breath, poor esthetic, denture stomatitis and angular cheilitis and the using of the denture cleanser is the solution for this problem but the prolong use of such cleansers may affect the properties of the denture. The aim of the study is to observe the effect of denture cleansers on color stability, water sorption and water solubility of the light cured acrylic resin after their immersion in tea solution. Light curing acrylic resin was prepared and immersed in four types of denture cleansers after there staining with tea then color stability, water sorption and water solubility of acrylic resin was measured. There were no changes in the stained acrylic properties when the samples were immersed in prepared denture cleansers and in the alkaline peroxide cleanser compared to that immersed in the distilled water in respect to color stability, sorption and solubility of the testing groups. The water sorption, water solubility and color stability of the light cured acrylic resin where immersed in the prepared denture cleanser solutions are in accordance with the American dental association no.12. The denture cleanser are good and satisfactory cleanser materials for the acrylic resin denture base and it’s recommended for cleansing the prostheses which are cured by light curing method.